An analysis on the ASEAN agreement on transboundary haze pollution / Nurain Sharum … [et al.] - Sharum, Nurain; Desa, Nurul Azhariah; Hassan, Umi Izzati; Azizi, Nurul Adillia (Faculty of Law, 2014)
The issue of transboundary haze in Southeast Asia has been a prolonged issue since 1980. Southeast Asia had been suffering from haze since the past few decades. Many steps had been made by ASEAN (Association of South East Asian Nation) in resolving the issue of haze. As one of the efforts in mitigating this problem, ASEAN has established a treaty called The ASEAN Agreement on Transboundary Haze Pollution which supposedly to govern the act of each ASEAN members concerning to the matter of haze pollution. On the surface, this treaty is fairly similar with several previous haze pollution treaties and environmental protection treaties which seem to be effective, for instance; the Protocol on Environmental Protection to the Antarctic Treaty 1991. However, due to several reasons, the ASEAN Agreement on Transboundary Haze Pollution is not as effective as the other treaties in resolving the problems with regard to haze pollution. Therefore, this study will analyse on all aspects of the ASEAN Agreement on Transboundary Haze Pollution that governs on the matters of haze pollution and reasons to its ineffectiveness. This was done by comparing with other treaties.